Performance of Priestley–Taylor model for estimating evaporation with and without snow coverage over a temperate meadow in Inner Mongolia, China. (5th September 2018) - Chen, NiNa; Zhang, YuShu; Jin, ChangJie; Wang, AnZhi; Guan, DeXin; Mi, Na; Zhou, Bin
Abstract: To promote the awareness of Priestley–Taylor (PT) model and extend the knowledge of hydrological model under snow, performance of PT model was illustrated by comparing with eddy covariance (EC) measurements over a temperate meadow. The results showed that the mean half‐hourly averages and directly calculated daily value of PT parameter α is 0.47 ± 0.27 and 0.51 ± 0.32, respectively. Vapour pressure deficit VPD is the mainly factor influences α in the snow‐covered period, while soil moisture in the snow‐free period. PT method underestimated evaporation in the whole study period and showed remarkable difference in different phases. It performed best in the snow‐melting phase, better in the presnow phase, worse in the fresh snow phase and worst in the snow‐melted phase. These studies indicated that PT model could be used to estimate evaporation over temperate meadow in dormant season, but utility of a variable PT parameter α during different phases should be considered.